WEB-BASED APPLICATION FOR REGISTRATION AND MANAGEMENT OF ‘HAK KEKAYAAN INTELEKTUAL’ IN THE LRPM DEPARTMENT PRESIDENT UNIVERSITY - Fauzia Hanifah; Genta Sahuri (IT for Society, 2021)
Copyright is needed by everyone. They can file a copyright for a work they own to the government. If the submitted work has received a certificate of ownership rights to the work, then every person copying the work that is already certified will get a fine as regulated in the Undang – Undang Nomer 28 Tahun 2004 on copyright. President University has a department that manages and processes copyrights submitted by lecturers, employees or students on campus. In the process, currently only using a manual process, namely by face to face to submit a copyright application form. Not only that, the LRPM, the copyright filing manager, still uses the storage system on his computer and this makes his computer easy to experience problems because too much data is stored. From here an idea is created that can help make the process run fast, doesn't take a long time and reduces the problems that exist in storing approved forms. This application can also help creator to see the progress of copyright submissions digitally and download e-certificate files digitally, as well as fill out submission forms digitally. This can also serve to reduce the use of existing paper. For LRPM, they can easily see the neatly arranged storage according to the time of submission without downloading the scanned form. Process form submissions quickly and can upload e-certificates in the submitting platform.